Factors That Influence The Acquisition of Basic Biology Subject Values In Semester I Students at STIKes Salsabila Serang - Albahra, Albahra; Fathiyati, Fathiyati; Nasrullah, M. Hudzaifah (Akademi Keperawatan RSPAD Gatot Soebroto, 2021)
The purpose of this study was to determine several factors that affect the acquisition of grades in Basic Biology courses in semester 1 students at STIKes Salsabila Serang. This research is an analytical study with a cross sectional approach (cross sectional). Based on the results of the study, it is known that 41% of the first semester students of STIKes Salsabila Serang get less grades. Students with a continuous learning style will have 4 times the chance to get good grades in basic biology courses compared to students whose learning styles the day before the exam. Students who have attention will have 5 times the chance to get good grades in Basic Biology compared to students who do not pay attention. Students with interest will have a 4 times chance of getting good grades in Basic Biology compared to students who have no interest. Students with good motivation will have the opportunity 1 time to get a good grade in Basic Biology compared to students with poor motivation.